2015
DOI: 10.3852/14-096
|View full text |Cite
|
Sign up to set email alerts
|

Priority of Lophophacidium over Canavirgella: taxonomic status of Lophophacidium dooksii and Canavirgella banfieldii, causal agents of a white pine needle disease

Abstract: In 2009 unusual white pine needle discoloration was observed in eastern Canada and northeastern USA. While the symptoms were similar in most pine stands, the disease was diagnosed as Canavirgella banfieldii in several locations and Dooks needle blight caused by Lophophacidium dooksii in others. Because of the similarities in symptom development and morphological characters of the causal agents, it was suspected that C. banfieldii and L. dooksii are either the same or closely related species. To test this hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Their findings indicated that Lecanosticta acicola (previously known as Mycosphaerella dearnessii ) (Quaedvlieg et al ., ), the cause of brown spot needle blight, was the primary pathogen contributing to needle defoliation. Two needle cast fungi Lophophacidium dooksii (previously known as Canavirgella banfieldii (Laflamme et al ., ) and Bifusella linearis (Minter & Millar, ), and a putative new species of Septorioides , described as Septorioides strobi (Wyka & Broders, ) were also associated with defoliation events of P. strobus throughout the northeastern United States (Broders et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Their findings indicated that Lecanosticta acicola (previously known as Mycosphaerella dearnessii ) (Quaedvlieg et al ., ), the cause of brown spot needle blight, was the primary pathogen contributing to needle defoliation. Two needle cast fungi Lophophacidium dooksii (previously known as Canavirgella banfieldii (Laflamme et al ., ) and Bifusella linearis (Minter & Millar, ), and a putative new species of Septorioides , described as Septorioides strobi (Wyka & Broders, ) were also associated with defoliation events of P. strobus throughout the northeastern United States (Broders et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Lophophacidium dooksii is an obligate pathogen of Pinus strobus, placed in Lophophacidium despite morphological differences such as a melanised pseudoparenchymatous stroma continuous along the length of the ascoma versus the discontinuous, two-layered covering stroma of L. hyperboreum (Corlett and Shoemaker 1984). Excluding the amyloid ascus apex, the ascoma and asexual state (=Canavirgella banfieldii) morphology of L. dooksii are evocative of the Rhytismataceae, a relationship supported by a recent ITS phylogenetic analysis (Laflamme et al 2015). DNA sequences of L. hyperboreum are currently unavailable, but should be generated from new collections to determine its phylogenetic placement.…”
Section: Discussionmentioning
confidence: 99%
“…These two fungi can be distinguished by the shape of their hyaline ascospores. Bifusella linearis ascospores are constricted in the middle [17], whereas L. dooksi ascospores are oval [6,7]. Lecanosticta acicola produces acervular, erumpent, brown conidiomata ( Figure 2C) and solitary, brown conidia that are straight to curved, and subcylindrical [18][19][20].…”
Section: Morphologic Diversity Of Fungi Associated With Wpndmentioning
confidence: 99%
“…Needles of both mature trees and regeneration were damaged. Preliminary diagnosis of this foliar damage has been attributed to frost and two foliar diseases, brown spot needle blight caused by the fungus Lecanosticta acicola (formerly known as Mycosphaerella dearnessii) [5] and Canavirgella needle cast caused by C. banfieldii, recently determined to be the same species as Lophophacidium dooksii [6] and herein referred to as L. dooksii as that name has precedence. Diagnosing the damage agent is difficult because both fungi cause similar symptoms, although they can be differentiated by their sexual and asexual fruiting bodies produced at different times in the growing season.…”
Section: Introductionmentioning
confidence: 99%